2020
DOI: 10.1080/10402004.2020.1770389
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Sensor for Water-Contaminated Grease

Abstract: A simple and inexpensive corrosion sensor was manufactured to study the corrosion rate of new and water-contaminated lubricating grease using a galvanic cell. A galvanic charge was developed between electroless nickel immersion gold (ENIG) and zinc, manufactured by selectively plating on a custom manufactured interdigitated printed circuit board. This article shows the methodology in using this concept for any application that may require quantifying the corrosivity of a liquid or semisolid that could be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…However, the device did not distinguish between metals and other types of particles because the debris grains all have similar dielectric constants, and the microchannels made the monitor capability poor. To improve the failure of lubricants, Dittes et al [ 204 ] made a corrosion sensor ( Figure 27 ). The sensor consisted of a primary cell with chemically plated nickel-impregnated gold and a zinc electrode.…”
Section: Research On Bearings Lubrication Technology Of Wind Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…However, the device did not distinguish between metals and other types of particles because the debris grains all have similar dielectric constants, and the microchannels made the monitor capability poor. To improve the failure of lubricants, Dittes et al [ 204 ] made a corrosion sensor ( Figure 27 ). The sensor consisted of a primary cell with chemically plated nickel-impregnated gold and a zinc electrode.…”
Section: Research On Bearings Lubrication Technology Of Wind Turbinementioning
confidence: 99%
“… Sensor figures (ENIG and zinc coating indicated by gold and white traces) (Reprinted with permission from Ref. [ 204 ]. Copyright 2020 Taylor & Francis Group, LLC).…”
Section: Figurementioning
confidence: 99%
“…Luo et al [20,21] found from the test that after water is mixed in the lubricate, as the water content increases, the viscosity of the oil-water two-phase fluid first increases and then decreases rapidly, reaching a maximum at a water content of about 30%. Dittes et al [22] studied the corrosivity of water contamination of lubricating oils, and the corrosion rate increased proportionally as the water content in the lubricant increased from 0.3% to 5.0%. Lu et al [23] found that the coefficient of friction increases with increasing free water content under oil lubrication conditions, causing severe wear, deformation, and oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [20,21] found from the test that after water is mixed in the lubricant, with the water content increases, the viscosity of the oil−water two−phase fluid increases first and then decreases rapidly, reaching a maximum water content of about 30%. Dittes et al [22] studied the corrosivity of water contamination of lubricating oils, and they found the corrosion rate increased proportionally as the water content in the lubricant increased from 0.3% to 5.0%. Lu et al [23] found that the coefficient of friction increases with increasing free water content under oil lubrication conditions, causing severe wear, deformation, and oxidation.…”
Section: Introductionmentioning
confidence: 99%